Should Water Birth Be Offered as an Option for Childbearing Women?. Issue 4 (July 2015) - Beal, Judy; Shaw-Battista, Jenna; Huwe, Valerie Yates
Abstract : Is birth underwater safe? These experts present their views on this controversial childbirth method being offered by some providers and hospitals.